Communication Behavior of Students Using Online Games Reviewed from the Values of Islamic Religious Education at SMP Negeri 1 Depapre (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to describe the oral communication language model used by students who frequently play online games. Analyze student communication behavior while playing online games by examining it based on the values of Islamic Religious Education. This study uses a qualitative research approach with the type of field research, namely research that aims to understand the phenomena experienced by the research subjects thoroughly through descriptions in the form of words in natural conditions. The study was conducted at SMP Negeri 1 Depapre, Jayapura Regency with a focus on knowing student communication behavior, use of study time, learning motivation, and the ability to control emotions while playing online games reviewed from the values of Islamic Religious Education. Data collection was carried out through observation, interviews, and documentation with researchers. Data analysis techniques used an interactive analysis model. Based on the results of the study, students of SMP N.1 Depapre are very fond of playing online games so that they spend more time playing than studying and socializing. This has an impact on their behavior, such as using harsh language, not respecting time, low learning motivation, and difficulty controlling emotions, which are not in accordance with the values of Islamic Religious Education. Solutions to overcome negative behavior due to online games require cooperation between parents, schools, and the community. Parents limit playing time, schools provide supervision and education, and communities provide positive activities so that children do not become too dependent on online games.